Continued demographic shifts in hospitalised patients with COVID-19 from migrant workers to a vulnerable and more elderly local population at risk of severe disease. (February 2023) - Ngiam, Jinghao Nicholas; Chhabra, Srishti; Goh, Wilson; Sim, Meng Ying; Chew, Nicholas WS; Sia, Ching-Hui; Cross, Gail Brenda; Tambyah, Paul Anantharajah
Highlights: In 2020, COVID-19 predominantly affected young migrant workers in Singapore. Therefore, a low incidence of severe complications was observed in 2020. In 2021, COVID-19 affected Singapore's more elderly and vulnerable local population. Consequently, there was a greater strain on intensive care facilities in 2021. Monitoring COVID-19 demographic shifts help guide healthcare resource allocation. Abstract: Objectives: In the early months of the COVID-19 pandemic in Singapore, the vast majority of infected persons were migrant workers living in dormitories who had few medical comorbidities. In 2021, with the Delta and Omicron waves, this shifted to the more vulnerable, elderly population within the local community. We examined evolving trends among the hospitalised cases of COVID-19. Methods: All patients with polymerase chain reaction-positive SARS-CoV-2 admitted from February 2020 to October 2021 were included and subsequently stratified by their year of admission (2020 or 2021). We compared the baseline clinical characteristics, clinical course, and outcomes. Results: A majority of cases were seen in 2020 (n = 1359), compared with 2021 (n = 422), due to the large outbreaks in migrant worker dormitories. Nevertheless, the greater proportion of locally transmitted cases outside of dormitories in 2021 (78.7% vs 12.3%) meant a significantly older population with more medical comorbidities had COVID-19. This led to an observably higher proportion of patients with severe disease presenting with raised inflammatory markers, need for therapeutics, supplemental oxygenation, and higher mortality. Conclusion: Changing demographics and the characteristics of the exposed populations are associated with distinct differences in clinical presentation and outcomes. Older age remained consistently associated with adverse outcomes.